Syntax mluvené češtiny: kondenzance - Jiři Zeman (Stylistyka, 2020)
The article is oriented towards the presentation of some specific aspects of Czech spoken syntax, namely condensation. The material upon which the features of the syntactic structures and the manner of dividing the dialogue into various units are demonstrated consists of authentic informal conversations.